2019
DOI: 10.1039/c9na00393b
|View full text |Cite
|
Sign up to set email alerts
|

A low Schottky barrier height and transport mechanism in gold–graphene–silicon (001) heterojunctions

Abstract: ResiScope mapping showing the strong reduction of resistance induced by a graphene sheet inserted between silicon and gold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…The results are also in agreement with those of Zhong et al [ 28 ], who found a decrease in when a graphene layer was inserted into a GaN SBD. According to Courtin et al [ 22 ], a similar variation for a graphene–silicon interface was obtained. Inaba et al [ 29 ] also found a very low at a CNT–SiC interface.…”
Section: Resultssupporting
confidence: 56%
See 2 more Smart Citations
“…The results are also in agreement with those of Zhong et al [ 28 ], who found a decrease in when a graphene layer was inserted into a GaN SBD. According to Courtin et al [ 22 ], a similar variation for a graphene–silicon interface was obtained. Inaba et al [ 29 ] also found a very low at a CNT–SiC interface.…”
Section: Resultssupporting
confidence: 56%
“…As the graphene workfunction increased from 4 to 4.8 eV, the output current was affected ( Figure 9 ) and increased from 0.320 eV to 0.545 eV as presented in Figure 10 . This increase in can be interpreted according to the simple Schottky–Mott model as the difference between the workfunction of graphene ( ) and the affinity of β- ( ) [ 22 ]: …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the role played by the MIGS is much less clear when replacing the metal with a graphene layer. More specifically the Fermi level was found unpinned at the graphene/passivated-silicon interface [18,[28][29][30] indicating that the MIGS and the interface defect states density must be low (typically below 10 12 states/eV/cm 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many different new functionalities were observed such as bias-controlled Schottky barrier height [2,3] (SBH), photodetectors [4][5][6][7][8][9] or solar cells [10][11][12]. When covered with a metal, Metal/G/Si can be used as an efficient spin injector [13,14] or a low-resistance contact [15,16]. The reduction of the Si SBH is made possible by simultaneous etching of the silicon oxide and hydrogen passivation of the surface with graphene already on top [17].…”
Section: Introductionmentioning
confidence: 99%